Functional near-infrared spectroscopy of medical students answering various item types - Husain, Syeda Fabeha; Wang, Nixi; McIntyre, Roger S.; Tran, Bach X.; Nguyen, Thao Phuong; Vu, Linh Gia; Vu, Giang Thu; Ho, Roger C.; Ho, Cyrus S. (Frontiers in Psychology, 2023)
Background: Traditionally, the effect of assessment item types includingtrue/false questions (TFQ), multiple-choice questions (MCQ), short answer questions (SAQ) and case scenario questions (CSQ) are exmianed through psychometric qualities or student interviews. However, brain activity while answering such questions or items remains unknown. Functional near-infrared spectroscopy (fNIRS) can be used to safely measure cerebral cortex haemodynamic response during various tasks. Hence, this fNIRS study aimed to determine differences in frontotemporal cortex activity as medical students answered TFQ, MCQ, SAQ and CSQ. Methods: Twenty-four medical students (13 males and 11 females) were recruited in this study during their mid-psychiatry posting. Oxy-haemoglobin and deoxy-haemoglobin levels in the frontal and temporal regions was measured with a 52-channel fNIRS system. Participants answered 9-18 trials under each of the four types of tasks that were based on their psychiatry curriculum during fNIRS measurements. The area under the oxy-haemoglobin curve (AUC) for each participant and each item type was derived. Repeated measures ANOVA with post-hoc Bonferroni-corrected pairwise comparisons were used to determine differences in oxy-haemoglobin AUC between TFQ, MCQ, SAQ and CSQ. Results: Oxy-haemoglobin AUC was highest during the CSQ, followed by SAQ, MCQ and TFQ in both the frontal and temporal regions. Statistically significant differences between different types of items were observed in oxy-haemoglobin AUC of the frontal region (p < 0.001). Oxy-haemoglobin AUC in the frontal region was significantly higher during the CSQ than TFQ (p = 0.005) and during the SAQ than TFQ (p = 0.025). Although the percentage of correct responses was significantly lower in MCQ than other item types, there was no correlation between the percentage of correct response and oxy-haemoglobin AUC in both regions for all four item types (p > 0.05). Conclusions: CSQ and SAQ elicited greater haemodynamic response than MCQ and TFQ in the prefrontal cortex of medical students. This suggests that more cognitive skills may be required to answer CSQ and SAQ.